A kind of recycled concrete and preparation method thereof
By using the synergistic effect of components such as basalt fibers, polypropylene fibers, nano SiO2, nano CaCO3, steel fibers and silica fumes in recycled concrete, the problems of high porosity, poor density and low mechanical properties of recycled concrete are solved, and the problem of high porosity, poor density and low mechanical properties of recycled concrete is achieved. The effect of significantly reducing porosity and improving mechanical properties is achieved.
Patent Information
- Application Number
- CN202411514199.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-29
AI Technical Summary
Recycled concrete has high porosity, poor density and low mechanical properties, making it difficult to effectively replace natural aggregates.
Optimize the pore structure by suppressing bubble merging by using the network structure formed by basalt fibers and polypropylene fibers in recycled concrete; improve the density and interface transition zone performance using the synergistic effect of nano-SiO2 and nano-CaCO3; combine the high elastic modulus of steel fibers with high elastic modulus Obstruct microcrack expansion and macroscopic crack generation; add silicon fume to compensate for the weakening effect of the bond interface, and optimize the microstructure through magnesium oxide expansion agent and sodium hexametaphosphate.
It significantly reduces the porosity of recycled concrete, improves its density and mechanical properties, and enhances the denseness and crack resistance of the structure.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the field of concrete, and more particularly, to a recycled concrete and a preparation method thereof. Background Art
[0002] In the process of urban construction, construction waste such as abandoned concrete will be generated, accounting for about 30-40% of the total urban waste, which not only occupies land resources, but also causes environmental pollution. In addition, due to the excessive exploitation and large-scale use of raw materials such as sand and gravel aggregates used in construction projects, the shortage of construction raw materials has been caused. Therefore, the recycling and recycling technology of construction waste has become particularly important in today's construction projects. Crushing construction waste into recycled aggregates with grading requirements to replace natural aggregates can effectively alleviate the problems of overload of construction waste and shortage of natural resources. However, compared with natural aggregates, recycled aggregates have more microcracks, high porosity, and adhesion of old mortar, resulting in higher porosity, poorer density, and lower mechanical properties of the recycled concrete. Summary of the invention
[0003] In order to solve the above technical problems, the present application provides a recycled concrete and a preparation method thereof.
[0004] In the first aspect, the present application provides a recycled concrete, which adopts the following technical solution:
[0005] A recycled concrete, the raw materials used include the following components in parts by weight:
[0006] Recycled coarse aggregate 1150-1160 parts;
[0007] Regeneration micro powder 73.5-76.5 parts;
[0008] 490-510 parts of cement;
[0009] Basalt fiber 2.5-3.2 parts;
[0010] Polypropylene fiber 0.8-0.9 parts;
[0011] Steel fiber 7.35-7.65 parts;
[0012] Silica fume 49-51 parts;
[0013] Nano-SiO2 4.8-5.2 parts;
[0014] Nano-CaCO3 14.7-15.3 parts;
[0015] Alkaline activator 29.4-30.6 parts;
[0016] Water reducing agent 4.9-5.1 parts;
[0017] 250-260 parts of water.
[0018] By adopting the above technical scheme, the present application utilizes the network structure formed by basalt fiber and polypropylene fiber to inhibit the merging of bubbles in the mixing process of recycled concrete, optimizes the internal pore structure, and utilizes the synergistic effect of nano-SiO2 and nano-CaCO3 to greatly improve the compactness of recycled concrete and the performance of the interface transition zone, improves the density of the structure in microscopic size, and promotes the bridging between the fiber and the cement base through the coupling effect, thereby achieving the purpose of slow cracking and strengthening. And it also utilizes the characteristics of high elastic modulus of steel fiber to effectively hinder the expansion of microcracks in recycled concrete and the generation of macro cracks, thereby enhancing the mechanical properties of recycled concrete. The addition of silica fume can effectively compensate for the negative impact of the weakening effect of the bonding interface after the addition of steel fiber on recycled concrete. The filling and volcanic ash effect of silica fume can effectively improve the microstructure of recycled concrete, improve the compactness of recycled concrete, reduce the porosity of recycled concrete, and further enhance the mechanical properties of recycled concrete.
[0019] In addition, in addition to using recycled coarse aggregate to replace natural coarse aggregate, this application also adds a certain amount of recycled micropowder, which effectively recycles construction waste. The recycled micropowder is fine particles with a particle size of less than 0.15 mm produced during the crushing process of waste concrete. At the same time, an alkaline activator is used to stimulate the activity of the recycled micropowder, so that the recycled concrete has higher mechanical properties.
[0020] Preferably, the raw material comprises the following components in parts by weight:
[0021] 1155 parts of recycled coarse aggregate;
[0022] Regeneration micro powder 75 parts;
[0023] 500 parts of cement;
[0024] 2.85 parts of basalt fiber;
[0025] 0.85 parts of polypropylene fiber;
[0026] 7.5 parts of steel fiber;
[0027] Silica fume 50 parts;
[0028] Nano-SiO2 5 parts;
[0029] Nano-CaCO3 15 parts;
[0030] 30 parts of alkaline stimulant;
[0031] 5 parts of water reducing agent;
[0032] 255 parts of water.
[0033] By adopting the above technical solution, the present application further optimizes the usage of each raw material in the recycled concrete, promotes the synergistic effect between the components, thereby further reducing the porosity of the recycled concrete and improving the mechanical properties of the recycled concrete.
[0034] Optionally, the alkaline activator is one of sodium hydroxide, calcium hydroxide and liquid water glass.
[0035] Preferably, the alkaline activator is calcium hydroxide.
[0036] The sodium hydroxide, calcium hydroxide and liquid water glass of the present application can significantly stimulate the activity of the recycled micropowder, thereby improving the mechanical properties of the recycled concrete. Experimental data show that compared with sodium hydroxide and liquid water glass, calcium hydroxide has a better stimulating effect on the recycled micropowder, and the mechanical properties of the recycled concrete finally obtained are stronger.
[0037] Preferably, the raw materials further include magnesium oxide expansion agent and sodium hexametaphosphate, the amount of the magnesium oxide expansion agent is 3-6% of the weight of the cement, and the amount of the sodium hexametaphosphate is 0.15-0.3% of the weight of the cement.
[0038] Preferably, the dosage of the magnesium oxide expansion agent is 6%, and the dosage of the sodium hexametaphosphate is 0.15% of the weight of the cement.
[0039] By adopting the above technical scheme, the present application also uses the hydration product of magnesium oxide expansion agent to fill the slurry pores, so that the interface transition zone between slurry and aggregate is more compact, the porosity of recycled concrete is reduced, and the mechanical strength of recycled concrete is improved. At the same time, sodium hexametaphosphate is used to make up for the defects of magnesium oxide expansion agent that makes slurry fluidity worse and reduces the workability of recycled concrete, and further improves the mechanical properties of recycled concrete. However, the addition of sodium hexametaphosphate will weaken the expansion effect of magnesium oxide expansion agent, so the present application further optimizes the usage of magnesium oxide expansion agent and sodium hexametaphosphate, so that recycled concrete can have higher mechanical properties.
[0040] Preferably, the raw materials further include a self-healing agent in an amount of 0.3-0.5% by weight of the cement.
[0041] By adopting the above technical scheme, the present application also adds a certain amount of self-healing agent, and utilizes the synergistic effect between the self-healing agent and other components to delay the occurrence of cracks in the recycled concrete and realize self-healing of the cracks, thereby effectively improving the structural durability of the recycled concrete and extending the service life of the recycled concrete.
[0042] Preferably, the self-healing agent is prepared by mixing calcium oxide expansion agent, Na-bentonite and talcum powder as core material, and water glass activated metakaolin as wall material.
[0043] By adopting the above technical solution, the healing agent has no effect on the matrix when there are no cracks and is well preserved. When cracks occur, the cracks expand and cause the wall material to rupture. Water and other substances that enter from the outside can react chemically with the core material to produce functional substances with good compatibility with the cement matrix, filling and repairing the cracks, while at the same time restoring the strength of the repaired matrix.
[0044] Among them, calcium oxide expansive agent has a crystallization expansion effect, which can improve the density of recycled concrete during self-repair; Na-bentonite has strong water absorption, and while the matrix cracks and absorbs water to expand, it can also provide the water required for continuous hydration of the expansive material; talcum powder can not only make up for the adverse effect of Na-bentonite water absorption on water migration, but also provide a large amount of magnesium ions and silicate ions, which is conducive to the formation of hydrated calcium silicate and high-strength magnesium products, thereby improving the overall strength of the matrix after crack repair; water glass-activated kaolin is not only easy to form a film, but also has good compatibility with the cement matrix.
[0045] In a second aspect, the present application provides a method for preparing recycled concrete, comprising the following steps:
[0046] Under the conditions of a temperature of 20-30°C and a rotation speed of 300-350r / min, all the raw materials are mixed and stirred for 30-40 minutes, and then poured and cured to obtain recycled concrete.
[0047] Preferably, the recycled coarse aggregate is treated with a nano-calcium silicate hydrate seed solution with a concentration of 5-7wt% before mixing.
[0048] By adopting the above technical scheme, the present application uses a certain concentration of nano calcium silicate hydrate seed solution to treat the recycled coarse aggregate, which can improve the surface properties of the recycled coarse aggregate, thereby enhancing the interface transition zone between the cement matrix and the recycled coarse aggregate, and further improving the mechanical properties of the recycled concrete.
[0049] In summary, this application has the following beneficial technical effects:
[0050] 1. The recycled concrete of the present application not only contains recycled coarse aggregate, but also contains a certain amount of recycled micro powder, which recycles abandoned buildings to a great extent and meets the requirements of sustainable development;
[0051] 2. The interface transition zone of the recycled concrete of this application has good performance, less porosity, higher density and stronger mechanical properties;
[0052] 3. The method for preparing recycled concrete of the present application has simple steps and is easy to operate, uses low-cost raw materials, has low production costs, and is suitable for large-scale production. DETAILED DESCRIPTION
[0053] The present application is further described in detail below with reference to the embodiments.
[0054] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available products.
[0055] Recycled coarse aggregate, using continuously graded crushed waste concrete blocks, the waste concrete blocks are taken from the old concrete removed from the construction site, crushed twice by a jaw crusher and then manually screened, and its apparent density is 1500kg / m 3 , the crushing value is 14.34, the water absorption is 3.33%, and the particle size range is 2-20mm.
[0056] Recycled micro powder is fine particles with a size less than 0.15mm produced during the crushing process of waste concrete.
[0057] As cement, P·O 42.5 ordinary Portland cement was selected.
[0058] Basalt fiber, diameter 17μm, length 12mm, density 2.8g / cm 3 , the tensile strength is >1050MPa, the elastic modulus is 40GPa, and the elongation at break is 3.50%.
[0059] Polypropylene fiber, diameter 40μm, length 12mm, density 0.91g / cm 3 , the tensile strength is >486MPa, the elastic modulus is 3.5GPa, and the elongation at break is 9.10%.
[0060] Steel fiber, using corrugated steel fiber, its equivalent diameter is about 0.65mm, length is 32mm, aspect ratio is 50, density is 7.9g / cm 3 , elastic modulus is 200GPa, and tensile strength is ≥1100MPa.
[0061] Silica fume, particle size is 0.2μm.
[0062] Water reducer, which is a polycarboxylic acid high efficiency water reducer.
[0063] Liquid water glass has an initial modulus of 3, and sodium hydroxide is added to adjust the modulus to 1.
[0064] Magnesium oxide expansion agent, which is S-type light-burned magnesium oxide expansion agent;
[0065] The nano-hydrated calcium silicate seed solution is a white suspension obtained by adding a calcium source aqueous solution and a silicon salt aqueous solution to a polycarboxylate water-reducing agent for reaction. The average particle size of the suspension is 24.8 nm and the concentration is 20 wt %.
[0066] The self-healing agent is prepared by the following method: calcium oxide expansion agent, Na-bentonite and talc powder in a weight ratio of 5:2:2 are evenly mixed and added into a granulator to prepare composite spherical particles as core materials; kaolin, water and water glass in a weight ratio of 2:3:5 are mixed to obtain a wall material solution, and then the wall material solution is evenly sprayed onto the surface of the core material, and then the self-healing agent with a particle size range of 0.6-2.36 mm is obtained after drying and sieving.
[0067] Example 1.1
[0068] A method for preparing recycled concrete comprises the following steps:
[0069] At a temperature of 20°C and a rotation speed of 350r / min, 1150kg of recycled coarse aggregate, 76.5kg of recycled micropowder, 490kg of cement, 3.2kg of basalt fiber, 0.8kg of polypropylene fiber, 7.65kg of steel fiber, 49kg of silica fume, 5.2kg of nano-SiO2, 14.7kg of nano-CaCO3, 30.6kg of calcium hydroxide, 4.9kg of polycarboxylic acid high-efficiency water reducer and 260kg of water were mixed and stirred for 30 minutes, and then poured and cured to obtain recycled concrete.
[0070] Example 1.2
[0071] A method for preparing recycled concrete comprises the following steps:
[0072] At a temperature of 30°C and a rotation speed of 300r / min, 1160kg of recycled coarse aggregate, 73.5kg of recycled micropowder, 510kg of cement, 2.5kg of basalt fiber, 0.9kg of polypropylene fiber, 7.35kg of steel fiber, 51kg of silica fume, 4.8kg of nano-SiO2, 15.3kg of nano-CaCO3, 29.4kg of calcium hydroxide, 5.1kg of polycarboxylic acid high-efficiency water reducer and 250kg of water were mixed and stirred for 40 minutes, and then poured and cured to obtain recycled concrete.
[0073] Example 2.1
[0074] A method for preparing recycled concrete comprises the following steps:
[0075] Under the conditions of temperature of 30℃ and rotation speed of 300r / min, 1155kg recycled coarse aggregate, 75kg recycled micro powder, 500kg cement, 2.85kg basalt fiber, 0.85kg polypropylene fiber, 7.5kg steel fiber, 50kg silica fume, 5kg nano-SiO2, 15kg nano-CaCO3, 30kg calcium hydroxide, 5kg polycarboxylic acid high-efficiency water reducer and 255kg water were mixed and stirred for 40 minutes, and then poured and cured to obtain recycled concrete.
[0076] Example 3.1
[0077] A method for preparing recycled concrete, which is different from Example 2.1 in that calcium hydroxide is replaced by sodium hydroxide, and the rest is the same as Example 2.1.
[0078] Example 3.2
[0079] A method for preparing recycled concrete, which is different from Example 2.1 in that calcium hydroxide is replaced by liquid water glass, and the rest is the same as Example 2.1.
[0080] Example 4.1
[0081] A method for preparing recycled concrete, which is different from Example 2.1 in that 15 kg of magnesium oxide expansion agent is added and mixed evenly with cement and other components, and the rest is the same as Example 2.1.
[0082] Example 4.2
[0083] A method for preparing recycled concrete, which is different from Example 2.1 in that 30 kg of magnesium oxide expansion agent is added and mixed evenly with cement and other components, and the rest is the same as Example 2.1.
[0084] Example 4.3
[0085] A method for preparing recycled concrete, which is different from Example 2.1 in that: 15 kg of magnesium oxide expansion agent and 0.75 kg of sodium hexametaphosphate are added and mixed evenly with cement and other components, and the rest is the same as Example 2.1.
[0086] Example 4.4
[0087] A method for preparing recycled concrete, which is different from Example 2.1 in that: 15 kg of magnesium oxide expansion agent and 1.5 kg of sodium hexametaphosphate are added and mixed evenly with cement and other components, and the rest is the same as Example 2.1.
[0088] Example 4.5
[0089] A method for preparing recycled concrete, which is different from Example 2.1 in that: 30 kg of magnesium oxide expansion agent and 0.75 kg of sodium hexametaphosphate are added and mixed evenly with cement and other components, and the rest is the same as Example 2.1.
[0090] Example 4.6
[0091] A method for preparing recycled concrete, which is different from Example 2.1 in that: 30 kg of magnesium oxide expansion agent and 1.5 kg of sodium hexametaphosphate are added and mixed evenly with cement and other components, and the rest is the same as Example 2.1.
[0092] Example 5.1
[0093] A method for preparing recycled concrete, which is different from Example 2.1 in that: 1.5 kg of self-healing agent is further added and mixed evenly with cement and other components, and the rest is the same as Example 2.1.
[0094] Example 5.2
[0095] A method for preparing recycled concrete, which is different from Example 2.1 in that: 2.5 kg of self-healing agent is further added and mixed evenly with cement and other components, and the rest is the same as Example 2.1.
[0096] Example 6.1
[0097] A method for preparing recycled concrete, which is different from Example 2.1 in that: a 20wt% nano-calcium silicate hydrate seed solution is diluted with water to a concentration of 5wt%, and then evenly sprayed onto the surface of recycled coarse aggregate, and the spraying amount is the water absorption of the recycled coarse aggregate. Thereafter, the concrete is allowed to stand for 24 hours at a temperature of 20°C and a humidity of 40%, and then mixed with cement and other components. The rest is the same as Example 2.1.
[0098] Example 6.2
[0099] A method for preparing recycled concrete, which is different from Example 2.1 in that: a 20wt% nano-calcium silicate hydrate seed solution is diluted with water to a concentration of 7wt%, and then evenly sprayed onto the surface of recycled coarse aggregate, and the spraying amount is the water absorption of the recycled coarse aggregate. Thereafter, the concrete is allowed to stand for 24 hours at a temperature of 20°C and a humidity of 40%, and then mixed with cement and other components. The rest is the same as Example 2.1.
[0100] Example 6.3
[0101] A method for preparing recycled concrete, which is different from Example 2.1 in that: a 20wt% nano-hydrated calcium silicate seed solution is diluted with water to a concentration of 10wt%, and then evenly sprayed onto the surface of recycled coarse aggregate, and the spraying amount is the water absorption of the recycled coarse aggregate. Thereafter, the concrete is allowed to stand for 24 hours at a temperature of 20°C and a humidity of 40%, and then mixed with cement and other components. The rest is the same as Example 2.1. Comparative Example 1
[0102] The difference from Example 2.1 is that no alkaline activator is added, and the rest is the same as Example 2.1. Comparative Example 2
[0103] The difference from Example 2.1 is that no nano-CaCO3 is added, the amount of nano-SiO2 used is 20kg, and the rest is the same as Example 2.1. Comparative Example 3
[0104] The difference from Example 2.1 is that no nano-SiO2 is added, the amount of nano-CaCO3 used is 20kg, and the rest is the same as Example 2.1. Comparative Example 4
[0105] The difference from Example 2.1 is that the amount of nano-CaCO3 used is 20 kg, and the rest is the same as Example 2.1. Comparative Example 5
[0106] The difference from Example 2.1 is that no silica fume is added, and the rest is the same as Example 2.1. Comparative Example 6
[0107] The difference from Example 2.1 is that the amount of silica fume used is 60 kg, and the rest is the same as Example 2.1.
[0108] Performance Testing
[0109] 1. The porosity (%) of the recycled concrete specimens obtained after curing under standard conditions in the above-mentioned embodiments and comparative examples was tested with reference to "JGJ 55-2000 Ordinary Concrete Mix Design Code", and the test results are shown in Table 1;
[0110] 2. The 28d compressive strength (MPa) and 28d flexural strength (MPa) of the recycled concrete specimens obtained by curing under standard conditions in the above-mentioned embodiments and comparative examples were tested with reference to GB / T 50081-2002 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete". The test results are shown in Table 1.
[0111] 3. The compressive strength of the recycled concrete specimens obtained by curing for 28 days under standard conditions in Example 2.1 and Example 5.1-5.2 is recorded as the first compressive strength f0, and then pre-compressed to 80% of the corresponding f0 and placed in water for further curing for 28 days, and the second compressive strength f1 is measured, and the compressive strength recovery rate (%) is calculated according to γ=f1 / f0×100%, and the results are shown in Table 2;
[0112] 4. The recycled concrete specimens obtained by curing for 7 days under standard conditions in Example 2.1 and Examples 5.1-5.2 were subjected to crack suppression. Cracks with a width of 100-400 μm were selected, two points were measured for each crack, and the initial crack width (l0) was recorded. Then, the specimens were placed in water and cured for another 7 days. The crack width after re-curing (l1) was recorded, and the crack width healing rate (%) was calculated according to L=(l0-l1) / l0×100%. The results are shown in Table 2.
[0113] Table 1
[0114]
[0115] Table 2
[0116]
[0117] As can be seen from Table 1, the porosity of the recycled concrete specimens prepared in Examples 1.1-2.1 of the present application is 3.84-3.95%, which is far below the standard requirements, the 28d compressive strength is 48.41-49.16MPa, and the 28d flexural strength is 6.5-6.9MPa, which is far above the standard requirements. It can be seen that the recycled concrete of the present application can still have a lower porosity, a higher degree of compactness, and stronger mechanical properties when a large amount of abandoned buildings are added. Among them, compared with Example 1.2, Example 2.1 can further reduce the porosity of the recycled concrete, improve the compactness of the recycled concrete, and enhance the mechanical properties of the recycled concrete after further optimizing the ratio of each raw material.
[0118] Compared with Example 2.1, when calcium hydroxide is replaced by sodium hydroxide or liquid water glass, the porosity of the recycled concrete is increased, and the 28d compressive strength and 28d flexural strength are reduced. It can be seen that compared with sodium hydroxide and liquid water glass, calcium hydroxide has a better stimulating effect on the recycled micropowder.
[0119] Compared with Example 2.1, when the magnesium oxide expansion agent is further added in Examples 4.1-4.2, the porosity of the recycled concrete is significantly reduced, and the 28d compressive strength and 28d flexural strength are improved. It can be seen that the addition of magnesium oxide expansion agent can reduce the porosity of the recycled concrete and improve the mechanical properties of the recycled concrete.
[0120] Compared with Example 2.1, when magnesium oxide expansion agent and sodium hexametaphosphate are further added, the porosity of the recycled concrete is significantly reduced, and the 28d compressive strength and 28d flexural strength are improved. In addition, the degree of reinforcement of recycled concrete in Examples 4.3-4.6 is higher than that in Examples 4.1-4.2. It can be seen that the mixed use of magnesium oxide expansion and sodium hexametaphosphate can further reduce the porosity of recycled concrete and improve the mechanical properties of recycled concrete. In addition, compared with Examples 4.3-4.5, the porosity of the recycled concrete specimens prepared in Example 4.6 is slightly higher, and the 28d compressive strength and 28d flexural strength are slightly lower. It can be seen that the weakening of the expansion effect of sodium hexametaphosphate on the magnesium oxide expansion agent will be manifested when the magnesium oxide expansion agent is used in a high amount, thereby affecting the strengthening effect of the magnesium oxide expansion agent on the recycled concrete. Therefore, optimizing the use of magnesium oxide expansion agent and sodium hexametaphosphate can enable the recycled concrete to have higher mechanical properties.
[0121] Compared with Example 2.1, when the self-healing agent is further added, the porosity of the recycled concrete is reduced, and the 28d compressive strength and 28d flexural strength are improved. It can be seen that the addition of the self-healing agent can reduce the porosity of the recycled concrete and improve the mechanical properties of the recycled concrete. At the same time, combined with Table 2, it can be seen that the addition of the self-healing agent can significantly improve the compressive strength recovery rate and crack width healing rate of the recycled concrete, so that the recycled concrete has a strong self-healing ability and prolongs the service life of the recycled concrete.
[0122] Compared with Example 2.1, when the recycled coarse aggregate is further strengthened and then used, the porosity of the recycled concrete can be reduced, and the 28d compressive strength and 28d flexural strength can be improved. It can be seen that the use of nano-hydrated calcium silicate seed solution to treat the recycled coarse aggregate can improve the surface activity of the recycled coarse aggregate, thereby reducing the porosity of the recycled concrete and improving the mechanical properties of the recycled concrete. Among them, compared with Examples 6.1-6.2, Example 6.3 has a reduced strengthening effect on the recycled concrete. It can be seen that when the concentration of the nano-hydrated calcium silicate seed solution for treating the recycled coarse aggregate is too high, the crystal nucleus particles of the nano-hydrated calcium silicate seed solution are prone to agglomeration, thereby failing to play its role as a crystal nucleus between the recycled coarse aggregate and the new slurry, and failing to fully play the role of strengthening the interface transition zone between the recycled coarse aggregate and the new slurry.
[0123] Compared with Example 2.1, when no alkaline activator is added, the porosity of the recycled concrete increases significantly, and the 28d compressive strength and 28d flexural strength decrease significantly. It can be seen that the addition of the alkaline activator can significantly stimulate the activity of the recycled micropowder, thereby reducing the porosity of the recycled concrete and improving the mechanical properties of the recycled concrete.
[0124] Compared with Example 2.1, when the total amount of nanoparticles added is kept unchanged and only one of nano-CaCO3 and nano-SiO2 is used, the porosity of the recycled concrete increases, and the 28d compressive strength and 28d flexural strength decrease. It can be seen that the mixed use of nano-CaCO3 and nano-SiO2 can give full play to the synergistic effect between the two, thereby reducing the porosity of the recycled concrete and improving the mechanical properties of the recycled concrete.
[0125] Compared with Example 2.1, when the amount of nano-CaCO3 used is relatively large, the porosity of the recycled concrete increases, and the 28d compressive strength and 28d flexural strength decrease. It can be seen that excessive nano-CaCO3 will agglomerate inside the cement matrix, causing negative growth in the mechanical properties of the recycled concrete, and generating excessive low-carbon hydrated calcium aluminate, which will lead to an increase in pores and cracks, thereby reducing the modification effect of nano-CaCO3.
[0126] Compared with Example 2.1, in Comparative Examples 5-6, when no silica fume is added or too much silica fume is added, the porosity of the recycled concrete increases, and the 28d compressive strength and 28d flexural strength decrease. It can be seen that the appropriate amount of silica fume added can fully synergize with components such as steel fibers, thereby improving the mechanical properties of the recycled concrete. If excessive addition is made, agglomeration will occur in the steel fiber cement matrix, and more weak interfaces will be generated inside the steel fiber cement matrix after agglomeration, thereby reducing the modification effect of silica fume.
[0127] The embodiments of this specific implementation method are all preferred embodiments of the present application, and are not intended to limit the protection scope of the present application. Therefore, all equivalent changes made based on the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A recycled concrete, characterized in that: The raw materials used include the following components in parts by weight: Recycled coarse aggregate 1150-1160 parts; Regeneration micro powder 73.5-76.5 parts; 490-510 parts of cement; Basalt fiber 2.5-3.2 parts; Polypropylene fiber 0.8-0.9 parts; Steel fiber 7.35-7.65 parts; Silica fume 49-51 parts; Nano-SiO2 4.8-5.2 parts; Nano-CaCO3 14.7-15.3 parts; Alkaline activator 29.4-30.6 parts; Water reducing agent 4.9-5.1 parts; 250-260 parts of water; The alkaline activator is calcium hydroxide; The raw materials also include magnesium oxide expansion agent and sodium hexametaphosphate; The amount of the magnesium oxide expansion agent is 6% of the weight of the cement, and the amount of the sodium hexametaphosphate is 0.15% of the weight of the cement; The raw materials also include a self-healing agent in an amount of 0.3-0.5% by weight of cement; The self-healing agent is prepared by mixing calcium oxide expansion agent, Na-bentonite and talcum powder as core material and metakaolin activated by water glass as wall material.
2. The recycled concrete according to claim 1, characterized in that: The raw materials include the following components in parts by weight: 1155 parts of recycled coarse aggregate; Recycled micro powder 75 parts; 500 parts of cement; 2.85 parts of basalt fiber; 0.85 parts of polypropylene fiber; 7.5 parts of steel fiber; Silica fume 50 parts; Nano-SiO2 5 parts; Nano-CaCO3 15 parts; 30 parts of alkaline stimulant; 5 parts of water reducing agent; 255 parts of water.
3. A method for preparing recycled concrete according to claim 1, characterized in that: The following steps are involved: Under the conditions of a temperature of 20-30°C and a rotation speed of 300-350r / min, all the raw materials are mixed and stirred for 30-40 minutes, and then poured and cured to obtain recycled concrete.
4. The method for preparing recycled concrete according to claim 3, characterized in that: The recycled coarse aggregate is treated with a nano calcium silicate hydrate seed solution with a concentration of 5-7wt% before mixing.
Citation Information
Patent Citations
Modified recycled concrete and preparation method thereof
CN108726956A
Self-repairing concrete and preparation method thereof
CN110240457A